Studi Gaya Vintage pada Interior Cafe Di Surabaya. (Studi Kasus : Canary Cafe, DailySweet Cafe dan Stilrod Cafe) - Lia Monica Tejo; mariana wibowo (Intra, 2014)
Research studies is about the application of vintage style in some cafe in Surabaya aims to determine the application of vintage design styles contained in the interior of the cafe Carpentier Kitchen , Canary Cafe , Daily Sweet Cafe , and Stilroad Cafe . Research studies of vintage style design will be carried out in Surabaya with a case study that some cafe in Surabaya that meets the criteria of vintage design styles , including the Carpentier Kitchen , Canary Cafe , Daily Sweet Cafe , and Stilroad Cafe . The method used in this research is descriptive qualitative method . Since the purpose of the study was to determine the application of modern design vintage style cafe on the interior of each of which became a case study research . In collecting the data necessary literature studies , interviews , and direct observation to study the object . After the data is collected then proceed with data analysis methods and conclusions drawn in the end